FAKTOR-FAKTOR YANG MEMPENGARUHI KONSUMSI GENERASI MILENIAL KOTA DENPASAR DI MASA PANDEMI COVID-19 - Kirana, Anak Agung Istri Ratih; Yasa, I Gusti Wayan Murjana (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.10.NO.11.TAHUN.2021DO - 10.24843/EEB.2021.v10.i11.p01, 2021)
The aims of this study were: 1) to analyze the effect of the number of family members, education level, and income, simultaneously on food consumption, non-food consumption, and total consumption of Millennial Generation in Denpasar City; 2) analyze the effect of the number of family members, education level, and income, partially on food consumption, non-food consumption, and the total consumption of Millennial Generation in Denpasar City. This research was conducted in Denpasar City. The sampling technique used in this research is purposive sampling. Methods of data collection is done by observation, questionnaires, and interviews. The analysis technique used in this research is multiple linear regression. The results of this study indicate that the number of family members, education level, and income have a significant effect simultaneously on consumption. The number of family members and income have a significant positive effect on food consumption, education level has no significant effect on food consumption. The number of family members, education level and income have a significant positive effect partially on non-food consumption. The number of family members, education level and income partially have a significant positive effect on total consumption.